1994
DOI: 10.1007/bf02506892
|View full text |Cite
|
Sign up to set email alerts
|

Latinos and latinas in community psychology: A review of the literature

Abstract: Latinos and Latinas are one of the largest minority groups in the United States yet they remain a silent group. The article begins by considering the social, historical, and economic backgrounds of Latino and Latina groups in the U.S. as a context for understanding diversity and as a resource for explaining the participation of this minority group in community psychology. This article then examines the extent to which Latinos and Latinas are present and participate in community psychology throughout its public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
66
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 59 publications
5
66
1
Order By: Relevance
“…This rate is consistent with rates reported by other investigators for treatment seeking for psychological problems in minority groups (O'Sullivan, Peterson, Cox, & Kirkeby, 1989;Ying & Miller, 1992). There has been growing recognition in the mental health care field that minority populations do suffer from mental health problems and that their underuse of the mental health care system is not a function of less need for such care (Bernal & Enchautegui-de-Jesus, 1994;O'Sullivan & Lasso, 1992). Compared with White samples, minority groups are much less likely to seek treatment (Dew, Dunn, Bromet, & Schulberg, 1988).…”
Section: Introductionsupporting
confidence: 85%
“…This rate is consistent with rates reported by other investigators for treatment seeking for psychological problems in minority groups (O'Sullivan, Peterson, Cox, & Kirkeby, 1989;Ying & Miller, 1992). There has been growing recognition in the mental health care field that minority populations do suffer from mental health problems and that their underuse of the mental health care system is not a function of less need for such care (Bernal & Enchautegui-de-Jesus, 1994;O'Sullivan & Lasso, 1992). Compared with White samples, minority groups are much less likely to seek treatment (Dew, Dunn, Bromet, & Schulberg, 1988).…”
Section: Introductionsupporting
confidence: 85%
“…However, this study found that the representation of cultural minorities fell below the proportion of these groups within the United States. Similarly, Bernal and Enchautegui-de-Jesus (1994) examined the representation of the Latino and Latina community in the JCP and AJCP during the 1973-1992 period and found that only 3.7% of published articles focused on this group, which falls far below the proportion of this group in the population of the United States (Bernal & Enchautegui-de-Jesus, 1994). These authors note that the comparative paucity of articles devoted to diversity issues, especially among specific underserved groups, suggests a gap between the ideals and practice of community psychology, which suggests that the ongoing examination of the extent to which community psychology rhetoric of valuing diversity is translated into the focus of published work.…”
Section: Content and Methods Of Published Workmentioning
confidence: 94%
“…Several studies of trends in published research have been conducted on the most established journals in community psychology and community mental health (Angelique & Culley, 2003;Bernal & Enchautegui-de-Jesus, 1994;Loo, Fong, & Iwamasa, 1988;Lounsbury, Cook, Leader, Rubeiz, & Meares, 1979;Lounsbury, Leader, Mears, & Cook, 1980;Martin et al, 2004;Novaco & Monahan, 1980;Speer, Griggs, Gibson, Lubin, & Hughey, 1992). However, studies of this nature have been particularly scarce in the last decade, and no studies examining data sets of articles published in community psychology journals in the 2000s were identified.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…found a decreased concern for theory and an increased emphasis on individuals independent of their environments. Finally, Bernal and Enchautegui-de-Jesus 1994! examined AJCP and JCP from 1973, and found that 79% of articles did not include ethnic minorities in their samples.…”
mentioning
confidence: 98%